Discovery of Macrocyclic Pyrimidines as MerTK‐Specific Inhibitors. (9th January 2017) - McIver, Andrew L.; Zhang, Weihe; Liu, Qingyang; Jiang, Xinpeng; Stashko, Michael A.; Nichols, James; Miley, Michael J.; Norris‐Drouin, Jacqueline; Machius, Mischa; DeRyckere, Deborah; Wood, Edgar; Graham, Douglas K.; et al.
Abstract: Macrocycles have attracted significant attention in drug discovery recently. In fact, a few de novo designed macrocyclic kinase inhibitors are currently in clinical trials with good potency and selectivity for their intended target. In this study, we successfully engaged a structure‐based drug design approach to discover macrocyclic pyrimidines as potent Mer tyrosine kinase (MerTK)‐specific inhibitors. An enzyme‐linked immunosorbent assay (ELISA) in 384‐well format was employed to evaluate the inhibitory activity of macrocycles in a cell‐based assay assessing tyrosine phosphorylation of MerTK. Through structure–activity relationship (SAR) studies, analogue11 [UNC2541; ( S )‐7‐amino‐ N ‐(4‐fluorobenzyl)‐8‐oxo‐2, 9, 16‐triaza‐1(2, 4)‐pyrimidinacyclohexadecaphane‐1‐carboxamide] was identified as a potent and MerTK‐specific inhibitor that exhibits sub‐micromolar inhibitory activity in the cell‐based ELISA. In addition, an X‐ray structure of MerTK protein in complex with11 was resolved to show that these macrocycles bind in the MerTK ATP pocket. Abstract : Big ring specificity : A structure‐based drug design approach led to macrocyclic pyrimidines as potent Mer tyrosine kinase (MerTK)‐specific inhibitors. Through SAR studies, analogue11 (UNC2541) was identified as a key compound and exhibits sub‐micromolar inhibitory activity in cell‐based enzyme‐linked immunosorbent assays. In addition, an X‐ray structure of MerTK in complex with11 was resolved to show that these macrocycles bind in the MerTK ATP pocket.